UPAYA PENCEGAHAN RADIKALISME AGAMA DAN TERORISME MELALUI PEMILIHAN TEMA BAHAN AJAR PADA MATA KULIAH ENGLISH FOR ISLAMIC STUDIES - Sa'dulloh Muzammil (AT-TURATS, 2015)
Radicalism and terrorism are often connected to a misconception of religion’s teachings. It emerges since one or a group of persons learn a religion’s teachings from wrong sources. In other words, they gain information form wrong persons or wrong literatures. Most of those involve in striking terror are youngsters for that education is then considered as one of solutions to prevent radicalism and terrorism. Thus this article proposes an alternative to avoid youngsters from the misconception of religion’s teachings by providing and selecting themes of teaching material that inform about truthful religion’s view on radicalism and terrorism.